USE OF PROBLEM BASED LEARNING MODELS TO IMPROVE PRIMARY SCHOOL STUDENTS CRITICAL THINKING ABILITY - Satritama, Muhamad Ridwan; Altaftazani, Deden Herdiana; Nurfurqon, Faridillah Fahmi (Journal Of Educational Experts (JEE), 2024)
The background of this research is to improve the critical thinking skills of elementary school students by using the Problem Based Learning model. This research uses a mixed methods approach, with a sample of 5th-grade students and a population of 30, consisting of 14 female students and 16 male students. The data processing results show an average pretest score of 42.19, while the average posttest score is 86.28. Additionally, the normality test value for the pretest is 0.066, whereas for the posttest it is 0.50. Thus, in terms of significance, both values meet the normality test criteria of 0.05, meaning this research can be accepted. Qualitatively, this research is considered successful, with the note that there were difficulties or challenges faced, such as difficulties in understanding the learning material, and occasionally there are some students in a class whose understanding abilities are lacking. Therefore, the conclusion of this research is that there is an improvement with the implementation of the Problem Based Learning model.